Impact of Biochar Application on Chemical and Microbial Properties of Soil - Wigan, Minajoy B. (Future Science / FSH-PH Publications, 2023)
Biochar is a carbonaceous solid compound formed by high-temperature of organic waste. The quality of biochar produced is determined by pyrolysis conditions and the type of raw materials. This study focused on the evaluation of the impact of biochar application on soil chemical and microbial properties. Four types of biochar from corn cobs, sawdust, mud press, and rice hull were produced and their chemical composition (pH, Organic Matter, Organic Carbon, Total Nitrogen, Carbon: Nitrogen Ratio, Available Phosphorus, and Exchangeable Potassium) was analyzed. A pot experiment with five treatments [T1 - Pure Soil; T2 – Soil + corn cob biochar; T3 – soil + sawdust biochar; T4 – soil + mud press biochar; T5 – soil + rice hull biochar] replicated three times was arranged in a completely randomized design (CRD). An equal amount of soil was placed in pots and mixed with biochar at a ratio of fifty grams (50g) per one-thousand grams (1000g) of soil. A total of fifteen experimental pots were used in the study where each pot contains a soil-biochar mixture of one-thousand five-hundred grams (1500g). Pearson’s correlation coefficients were used to determine how the soils applied with biochar are affected after sixty days of incubation and determine how biochar sources were related. All four biochar from rice hull, corn cobs, mud press, and sawdust are all alkaline and contain comparable amounts of organic matter, organic carbon, pH, soil nitrogen, available phosphorus, and exchangeable potassium. The result of the study showed that biochar application significantly improved soil pH, soil organic matter content, soil organic carbon, and soil nitrogen content. Soils amended with biochar showed comparable amounts of available phosphorus and exchangeable potassium. The application of biochar in soils therefore can be considered a potential solution to enhance soil fertility for sustainable crop production.